Potensi Wisata Pantai Bahagia Nongsa Kota Batam Sebagai Obat Patah Hati Bagi Gen Z - Saputra, Bemby; Abdillah, Atma Raga; Hidayat, Rahmad (Journal of Tourism Sciences, Technology and Industry, 2023)
Pantai Bahagia is located in Nongsa area, located at RT 001 RW 006, Sambau, Nongsa, Batam City, Riau Islands. This article discusses the tourism potential at Pantai Bahagia, Nongsa, Batam, using qualitative research methods. The objectives of this research are to explore the 3A components of tourism, analyze SWOT, identify the young people who visit, and understand the reasons for the large number of heartbroken people who choose Pantai Bahagia as their healing destination. The results show that Pantai Bahagia has a diversity of tourist attractions, adequate supporting facilities, and good accessibility. In addition, this article explains why Pantai Bahagia was chosen as a place to overcome heartbreak, by illustrating that the beach provides an opportunity for introspection, reflection, and the creation of new memories in an atmosphere that supports the healing process.